How to Measure a Performance of a Collaborative Research Centre - Alona Zharova; Janine Tellinger-Rice; Wolfgang Karl Härdle (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2018)
New Public Management helps universities and research institutions to perform in a highly competitive research environment. Evaluating publicly financed research results improves transparency, helps in reflection and self-assessment, and provides information for strategic decision making. In this paper we provide empirical evidence using data from a Collaborative Research Centre (CRC) on financial inputs and research output from 2005 to 2016. After selecting performance indicators suitable for a CRC, we describe main properties of the data using visualization techniques. To study the relationship between the dimensions of research performance, we use a time fixed effects panel data model and fixed effects Poisson model. With the help of year dummy variables, we show how the pattern of research productivity changed over time after controlling for staff and travel costs. The joint depiction of the time fixed effects and the research project's life cycle allows a better understanding of the development of the number of discussion papers over time.
Keywords: C00; 330; Research Performance; Time Fixed Effects Panel Data Model; Fixed Effects Poisson Model; Network; Collaborative Research Centre